Analisis Laporan Arus Kas sebagai Alat untuk Menilai Kinerja Keuangan Perusahaan PT Kimia Farma Tbk Periode 2022-2024 - Natira Tuti Billing; Zhunita Pasampe; Yesi Resa Marana; Arini Lestari Aris; Rafiqah Asaf (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the cash flow statement as an important tool in assessing the financial performance of PT Kimia Farma Tbk for the period 2022–2024. The cash flow statement, which consists of cash flows from operating, investing, and financing activities, provides an objective and comprehensive overview of the company's liquidity, solvency, and cash management efficiency. The analysis shows that during the study period, PT Kimia Farma Tbk experienced fluctuations in cash flow across these three activities. In 2022–2023, there was an increase in cash and cash equivalents, reflecting relatively good operational performance and efficient fund management. However, in 2023–2024, cash decreased again due to a combination of factors, including increased capital expenditures, payment of obligations, and decreased revenue from operating activities. These findings confirm that optimal cash management is key to maintaining smooth operations and supporting strategic decision-making. The cash flow statement is considered capable of providing more accurate information regarding actual financial performance than relying solely on the income statement. This is because net income does not always reflect the cash available to finance operational and investment activities. Thus, the cash flow statement can serve as a primary reference for management, investors, creditors, and other stakeholders in evaluating financial strength, detecting potential liquidity risks, and planning future financial strategies. This research is expected to contribute to the financial literature, particularly regarding the importance of cash flow statement analysis as a basis for evaluating company performance, while also providing input for similar companies to prioritize healthy and sustainable cash management.